Selecting and describing your research instruments - McClure, Kelly S. (Concise guides to conducting behavioral, health, and social science research series., 2020)
"Emerging researchers are often surprised to learn that instrument selection is a complex and important step in the process of research design. The first of its kind, this concise guide explains how to identify appropriate instruments, select the best ones for the job, and properly describe the instruments so that others will know how and why they were chosen. Each chapter in the book focuses on a specific aspect of instrument selection, with illuminating examples and helpful worksheets to fill out along the way. Topics include pinpointing what to measure, types of instruments, resources for identifying instruments, organizing information and taking notes, describing instruments for different audiences, ethical issues, considerations around individual differences and diversity, consulting with advisors, and troubleshooting. This book is part of APA's Concise Guides to Conducting Behavioral, Health, and Social Science Research series. Aimed at undergraduate students in research methods courses or others with a lab or research project, each book describes a key stage in the research process. Collectively, these books provide a solid grounding in research from start to finish"--